2019
DOI: 10.1021/acs.analchem.8b05977
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Surface Charge Visualization of Human Hair

Abstract: The surface charge and topography of human hair are visualized synchronously at the nanoscale using scanning ion conductance microscopy (SICM), a scanning nanopipette probe technique that uses local ion conductance currents to image the physicochemical properties of interfaces. By combining SICM data with finite element method (FEM) simulations that solve for ion transport at the nanopipette under bias, one is able to quantitatively correlate colocated surface charge and topography. The hair samples studied he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 47 publications
4
31
0
Order By: Relevance
“…The shape of the damage patterns is qualitatively similar to that observed in previous AFM experiments. 23,28,43 Similar coverage surface coverage projections are also observed for water and n-hexadecane (Fig. 2 in the ESI) † .…”
Section: In Watersupporting
confidence: 68%
See 1 more Smart Citation
“…The shape of the damage patterns is qualitatively similar to that observed in previous AFM experiments. 23,28,43 Similar coverage surface coverage projections are also observed for water and n-hexadecane (Fig. 2 in the ESI) † .…”
Section: In Watersupporting
confidence: 68%
“…14 The outer layers of hair are of particular interest since adsorption of formulation components, as well as lubrication between hair fibres, will largely depend on its surface properties. 1 Experimental surface characterization of virgin and damaged human hair has included the measurement of wetting by means of liquid contact angles, [15][16][17][18][19][20] surface charge density [21][22][23] as well as surface topography and friction using the atomic force microscope (AFM) 8,20,24,25 and high-load nanotribometers. 26 These studies have shown that compared to virgin hair, damaged hair usually displays increased surface charge density, hydrophilicity, and friction.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning ion conductance microscopy (SICM) [1], as a member of the scanning probe microscope (SPM) [2], has been developing for thirty years since 1989 and applied to many areas, such as surface topography measurement [3], nanoscale operation [4], cell volume measurement [5], cell mechanical properties research [6], and cell dynamics research [7]. It has been widely used in life science, medicine, materials science, nanofabrication, and other fields.…”
Section: Introductionmentioning
confidence: 99%
“…The current magnitude is highly sensitive to nanopipette-substrate separation and local ion conductivity, including that arising from the double layer at charged interfaces, and can be used to probe (independently) topography and surface charge of a range of substrates. [13][14][15] Critical information about the ionic environment of the substrate -solution interface can be acquired by employing specific potential-time SICM scanning protocols, 16,17 in tandem with finite element method (FEM) simulations, as exemplified by the quantitative analysis of surface charge 15,16,[18][19][20] and for reaction mapping. 12,21 In this paper, we consider the use of SICM to characterize the ionic (bioelectrical) environment of single live bacterial cells.…”
Section: Introductionmentioning
confidence: 99%